Study of Substructures in SDSS Supercluster S[173+014+0082] - Malla, Janak Ratna; Saurer, Walter; Aryal, Binil (Journal of Nepal Physical Society, 2022)
We present magnitude, color, redshift and number density distributions of 1302 galaxies in the supercluster S[173+014+0082]. Our aim is to identify substructures and study their redshift maps. The visual magnitude distribution suggests that the supercluster is dynamically unstable. We found 3 substructures in the supercluster region having mean redshift 0.083, 0.085 and 0.090. An empirical relation be-tween the number of galaxies in the substructures and their mean redshift is observed.